2018
DOI: 10.3389/fphys.2018.00422
|View full text |Cite
|
Sign up to set email alerts
|

Various Bee Pheromones Binding Affinity, Exclusive Chemosensillar Localization, and Key Amino Acid Sites Reveal the Distinctive Characteristics of Odorant-Binding Protein 11 in the Eastern Honey Bee, Apis cerana

Abstract: Odorant-binding proteins (OBPs) are the critical elements responsible for binding and transporting odors and pheromones in the sensitive olfactory system in insects. Honey bees are representative social insects that have complex odorants and pheromone communication systems relative to solitary insects. Here, we first cloned and characterized OBP11 (AcerOBP11), from the worker bees antennae of Eastern honey bee, Apis cerana. Based on sequence and phylogenetic analysis, most sequences homologous to AcerOBP11 bel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 66 publications
1
13
0
Order By: Relevance
“…In other words, AcerOBP6 was a broad-spectrum binding protein, which had similar binding properties to those of other insect OBPs, such as AipsGOBP1 and AlepGOBP2 [31,32]. At the same time, several studies had reported OBP functions in A. cerana cerana including AcerOBP1, AcerOBP10, AcerOBP11, and AcerOBP15, in which AcerOBP1 and AcerOBP15 were the proteins that were mainly involved in pheromone binding [19,21,33,34]. In addition, this binding characteristic of AcerOBP6 was also consistent with the structure of the PBP-GOBP domain.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…In other words, AcerOBP6 was a broad-spectrum binding protein, which had similar binding properties to those of other insect OBPs, such as AipsGOBP1 and AlepGOBP2 [31,32]. At the same time, several studies had reported OBP functions in A. cerana cerana including AcerOBP1, AcerOBP10, AcerOBP11, and AcerOBP15, in which AcerOBP1 and AcerOBP15 were the proteins that were mainly involved in pheromone binding [19,21,33,34]. In addition, this binding characteristic of AcerOBP6 was also consistent with the structure of the PBP-GOBP domain.…”
Section: Discussionmentioning
confidence: 89%
“…AmelOBP14 is better tuned to monoterpenoid structures, and AmelOBP21 will bind the main components of the queen mandibular pheromone as well as farnesol [18]. Apart from that, AcerOBP11 could bind to bee pheromones and some floral volatiles [19]. According to a recent study, AcerOBP10 is involved in oxidative stress defense [20], and myrcene may be a ligand of AcerOBP15 [21].…”
Section: Introductionmentioning
confidence: 99%
“…PBP1 has a strong affinity for the (−)-enantiomer, while PBP2 has a higher affinity for the (+)-enantiomer. Furthermore, AcerOBP11 of the eastern honey bee, Apis cerana , also displayed distinct binding affinities with various similar pheromone components …”
Section: Resultsmentioning
confidence: 99%
“…Volatile molecules reaching the honeybee antennae enter the sensillar pores and diffuse through the sensillar lymph until they reach the OSNs’ dendritic membrane. The sensillar lymph prevents the OSNs’ dendritic terminals from drying, and contains olfactory binding proteins (OBPs) and odorant degrading enzymes (ODEs) (Chertemps et al 2015 ; Forêt and Maleszka 2006 ; Iovinella et al 2018 ; Song et al 2018 ; Vogt et al 1991 ; Younus et al 2014 ). OBPs are likely involved in facilitating the transition of the odorants from a gaseous to a liquid environment and in transporting them towards the olfactory receptors (Gomez-Diaz et al 2013 ; Laughlin et al 2008 ; Leal 2013 ), even if recent studies in Drosophila showed that deletion of the principal OBP genes does not impair odor transduction, suggesting that many OBP may not play an essential role in odorant-receptor interaction (Xiao et al 2019 ).…”
Section: Honeybee Olfactory Systemmentioning
confidence: 99%